Sustainable Reinforced Prestressed Alkali-Activated Concrete Beams Using Industrial Wastes: An Experimental Investigation - Urmil Dave; Thakkar, Sonal; Darshan Bhatol; Abhishek Chanda (International Journal of Sustainable Construction Engineering and Technology, 2025)
In an era where the sustainability of the construction industry is of prime importance, alternatives to cement are a matter of urgency. In today’s era, alkali-activated concrete (AAC) which is a widely researched area, offers a viable alternative to cement concrete; it has the potential to utilize industrial waste as source material. The current study delves into assessing the impact of prestressing force on both reinforced AAC and reinforced ordinary cement concrete (OPCC) beams.  Industrial wastes that serve as primary constituents for AAC are slag and fly ash, which in the present investigation are activated using sodium-based activators. The concrete is developed using ambient curing with a compression value of 40 MPa to achieve sustainability. Analysis of deflection, load-carrying capacity, and failure characteristics was conducted on the reinforced concrete beams in unprestressed and prestressed states, encompassing both reinforced AAC and reinforced OPCC variety of beams. In comparison to reinforced AAC beams, OPCC beams had 18.9% higher strength in flexure, but the deflection was 53.3% higher for AAC beams with rebars. In prestressing conditions of beams, the reinforced OPCC beams had 22.5% more load-carrying capacity compared to reinforced prestressed AAC beams but had 26.2% more deflection compared to reinforced OPCC beams. Thus, sustainable reinforced concrete beams can be manufactured from industrial waste, having very good flexural behavior and load-carrying capacity.